Menggali Potensi Kinerja: Tinjauan Pelatihan dan Manajemen Karir di Institusi Polisi - Affandi, Muhammad Khoer (Universitas Pendidikan Indonesia, 2023)
The police is a state institution whose role is to provide protection and maintain the security of society and the state. This is expalined in law No. 2 of 2002 concerning the National Police of the Republic of Indonesia, article 5 pragraph 1. To improve the professionalism of police performance, superior human resources are neede as the main movers in institutions. Training is closely related to increasing the intellectual abilities neede to carry out better job duties and functions. A future career for employees wjo can achieve it is also an effort made by the institution so that employees can improve their performance for the future of police institution. This research aims to determine and analyze the influence of training and career management on the performance of Sukabumi City Police employees. This research was conducted using a quantitative approach. The population was 772 people, with a sample of 200 people taken using the Slovin formula. Research data was obtained using a questionnaire that had been tasted for validity and reliability. Data analysis uses multiple regression after testing the analysis requirements. The research results show that separately, training and career management have a positive effect on employee performance. Meanwhile, training and career management simultaneously have a positive effect on employee performance.